The drivers of the success of Spanish Canoeing: an analysis of the efficiency of regional federations - Ricart Luna, B.; Monteagudo Chiner, P.; Pérez Puchades, V.; Cordellat Marzal, A.; Roldán Aliaga, A.; Blasco Lafarga, C. (Retos: nuevas tendencias en educación física, deporte y recreación, 2021)
Even though canoeing is not a particularly popular sport in Spain, it is one of the Olympic disciplines that has brought much success to the Spanish medal table. This high performance of Spanish canoeing could be attributed to the work of the clubs and regional federations (FFAA) which can optimise the scarce resources available to them, most of which come from public transfers. This study measures the efficiency of the Spanish autonomous canoeing federations (FFAAP) during the 2013-2016 Olympic cycle using the Data Envelopment Analysis (DEA) technique and the Malmquist index. A second analysis tries to identify the key factors that lead to the efficiency of the federations. The results show that, despite the significant differences between FFAAs, there is no single way to reach efficiency. In general, the availability of resources increases the chances of achieving results, while coaches and internal competition contribute to optimising the performance of available resources.